2013
DOI: 10.1073/pnas.1215907110
|View full text |Cite
|
Sign up to set email alerts
|

DNA supercoiling enhances cooperativity and efficiency of an epigenetic switch

Abstract: Bacteriophage λ stably maintains its dormant prophage state but efficiently enters lytic development in response to DNA damage. The mediator of these processes is the λ repressor protein, CI, and its interactions with λ operator DNA. This λ switch is a model on the basis of which epigenetic switch regulation is understood. Using single molecule analysis, we directly examined the stability of the CI-operator structure in its natural, supercoiled state. We marked positions adjacent to the λ operators with peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Using magnetic tweezers, Ding et al showed that (−) DNA supercoiling can encourage the formation of λ repressor (CI)-mediated loops in DNA (Ding et al 2014), which in turn prevent over-expression of this repressor protein so that the cell can still preserve sensitivity to conditions that trigger virulence (lysis). Norregaard et al (Norregaard et al 2013) developed a unique peptide nucleic acid (PNA)-based assay with a tethered particle tracking method (Norregaard et al 2014) and showed that the presence of DNA supercoils can greatly enhance the juxtaposition probability of λ repressor (CI) and, hence, significantly increase the efficiency and cooperativity of a λ epigenetic switch.…”
Section: Single Molecule Studies Of Transcription Under Dna Supercoilingmentioning
confidence: 99%
“…Using magnetic tweezers, Ding et al showed that (−) DNA supercoiling can encourage the formation of λ repressor (CI)-mediated loops in DNA (Ding et al 2014), which in turn prevent over-expression of this repressor protein so that the cell can still preserve sensitivity to conditions that trigger virulence (lysis). Norregaard et al (Norregaard et al 2013) developed a unique peptide nucleic acid (PNA)-based assay with a tethered particle tracking method (Norregaard et al 2014) and showed that the presence of DNA supercoils can greatly enhance the juxtaposition probability of λ repressor (CI) and, hence, significantly increase the efficiency and cooperativity of a λ epigenetic switch.…”
Section: Single Molecule Studies Of Transcription Under Dna Supercoilingmentioning
confidence: 99%
“…Under these conditions, extensive DNA bending may be particularly facilitated by energy stored in superhelical strain. Comparing facilitation of small and large DNA loops by negative supercoiling will be interesting [60, 61]. Perhaps future Monte Carlo simulations, coupled with experiments, will allow this supercoiling-looping relationship to be understood in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Bistability is discussed with respect to all-or-none cellular processes such as differentiation, proliferation, survival and apoptosis [1][2][3][4][5][6]. However, much evidence about reversible switches has been observed in the regulatory network in biological experiments [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 97%